(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Past seismic events, have repeatedly served as reminders of the hazards posed by unreinforced masonry parapets. These parapets can be found in old residential buildings as well as heritage sites serving a great source of tourist attraction. Observed failure modes have revealed several cases where adopted retrofit techniques were inadequate to effectively secure parapets during earthquake-induced vibrations. This paper reviews shake table testing done for the dynamic behavior of masonry parapets. Parapet construction and retro-fit procedures are presented, followed by a discussion of the developed failure modes as well as the response of the retrofitted parapets.